Aplicación web responsiva para la gestión de ventas en establecimientos comerciales no especializados dedicados a la venta de productos básicos de la canasta familiar - Ruiz Cárdenas, Luis Carlos; Siabato Fonseca, Joan Sebastián (Universidad Antonio Nariño, 2022)
The implementation of new technologies have changed and evolved our lifestyles and this reveals those small companies that do not have easy access to the use of technology due to its high costs and/or complexity of use; In order to contribute to its evolution, it is necessary to develop a web application that mainly encourages local microenterprises to adopt technological tools, which help streamline the entire sales process; allowing the administrator to control his inventory, modify it and make it accessible digitally for the user's purchase; In the same way, the buyer will be able to self-manage all their purchases, generating a payment receipt to expedite the entire purchase legalization process and thus reduce the technology gap of small commercial establishments.